Implementasi Program Pengelolaan Bank Sampah Di Desa Larangan Kecamatan Candi - Risa Megariska; Hendra Sukmana (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
The purpose of this study is to describe and analyze the implementation of the waste bank program in Larangan Village, Candi District. The implementation of the Anggrek Waste Bank on waste management is a major focus of this study. The method used in this study is a qualitative descriptive method using primary and secondary data. Sources of data obtained online and offline, such as journals, the web, and information from sources. The results of this study suggest that the first standard dimensions and policy objectives of orchid waste Banks programs are having a positive impact on communities. The two dimensions of human resources contribute to the program and to financial resources can help the economic community. The three dimensions of communication are structured between management, depositors and cauldrons. Fourth, the characteristic dimension of the organization in the orchid waste bank program isa problem in determining the lift schedule and the granting of facilities from government agencies. Fifth, a dimension to the implementation of the program, and in social, economic, political environment it receives support from the external environment.